(untitled) (Práxis Educativa, 2021)
This paper is the result of our studies developed within the Study and Research Group on Countryside Education in the Amazon (Grupo de Estudos e Pesquisas em Educação do Campo na Amazônia - GEPERUAZ) about the contributions of Paulo Freire’s legacy to Education and Countryside School. The study is based on the premise that its backgrounds are intrinsically linked to Popular Education. For the elaboration of this text, we counted on a bibliographic and documentary study that supported the evidence presented, on the contributions of Freire’s theory to the understanding of the challenges that are imposed on education and on the Brazilian society today. The existing relations between Popular Education and Countryside Education translate into successful training/schooling initiatives that are underway in the face of the protagonism of the Countryside Education Movement in its 20 years of existence. Keywords: Freirean theory. Popular Education. Field Education.